The mediating effect of nursing informatics competency on the relationship between digital literacy and the problem-solving process among Korean nursing students: a cross-sectional study - Chang Seung Park; Yeong Ju Ko (Journal of Korean Biological Nursing Science, 2026)
Purpose: This study examined the effect of digital literacy on the problem-solving process among nursing students and tested whether nursing informatics competency mediated this relationship. Methods: This descriptive cross-sectional study included 119 nursing students. Data were analyzed using SPSS version 25.0 and PROCESS macro version 4.2, Model 4. The mediating effect was assessed using 5,000 bootstrap samples, and statistical significance was determined using the 95% confidence interval (CI). Results: Digital literacy was positively correlated with the problem-solving process (r = .63, p < .001). Digital literacy had a significant direct effect on the problem-solving process (c′= 0.33, p = .013), and nursing informatics competency had a significant indirect effect on this relationship (indirect effect = 0.38, 95% CI: 0.10–0.62). The direct effect of digital literacy on the problem-solving process remained significant after nursing informatics competency was included in the model, and the total effect was also significant (c = 0.71, p < .001). Conclusion: Digital literacy was directly and indirectly associated with the problem-solving process among nursing students, with nursing informatics competency serving as a significant mediating pathway. These findings suggest that educational strategies aimed at strengthening problem-solving abilities should address not only digital literacy but also nursing informatics competency. Future studies should test expanded models that include additional factors affecting the problem-solving process.